Synthesis of glycogen and poly (acrylic acid)-based graft copolymers via ATRP and its application for selective removal of Pb2+ ions from aqueous solution. (May 2015) - Pal, Aniruddha; Das, Dipankar; Sarkar, Amit Kumar; Ghorai, Soumitra; Das, Raghunath; Pal, Sagar
Graphical abstract: Highlights: Glycogen and poly (acrylic acid)-based graft copolymer was prepared via ATRP. Optimizing reaction parameters, well-defined copolymers with high Mn and low PDI were obtained. Copolymer removed Pb 2+ selectively and efficiently from various metal ions contaminated water. Abstract: We report the development of a novel graft copolymer, glycogen- graft-poly (acrylic acid) (g-Gly/pAA) with high molecular weight and low PDI, has been synthesized by ATRP using CuBr/bpy catalyst. The copolymer demonstrates its potential application for selective removal of Pb 2+ over other metal ions (Cd 2+, Cu 2+, Ni 2+ and Zn 2+ ). The hydroxyl groups present on glycogen were used to initiate the ATRP of acrylic acid (AAc). 1 H and 13 C NMR spectroscopic analyses predict the probable structure of copolymer and a likely mechanism for copolymer formation has been proposed. High molecular weight and low polydispersity index of g-Gly/pAA obtained from gel permeation chromatography signifies the controlled/living polymerization of AAc through ATRP. Surface properties of the copolymer have been investigated by field emission scanning electron microscopic (FESEM) analysis and elemental mapping. Rheological studies confirm the gel characteristics of g-Gly/pAA. Finally, g-Gly/pAA shows excellent potential to remove Pb 2+ selectively and efficiently from various metal ions contaminated water.